Starodubshchina: theoretical and methodological aspect of studying the border region in the early Modern period (second half of the 16th – 18th centuries) - Khrolenok, Evgeniy V. (Journal of the Belarusian State University. History, 2024)
The territory of Starodubshchina, a region located in the Belarusian-Russian-Ukrainian border area, is being investigated. Using the example of this region, theoretical and methodological problems related to the study of the history of the border area are considered. The necessity of applying a socio-psychological approach in the study, as well as the practices of a new local and social history (by giving the concept of «borderland» characteristics associated with the subject of history), is substantiated. The necessity of studying the boundary space, taking into account geographical and temporal factors, is emphasised. The geographical scope of the region was indicated during the early Modern period, when Starodubshchina was under the influence of different centres of gravity. At the same time, it is proposed to consider transformations affecting all spheres of life of the border society as the point of report of each of the stages of the stage in the history of the region. To localise the studied region in the second half of the 16th century, the historical and geographical term «Starodubskaya Severschyna» is introduced. Special attention is paid to the connection of the region with the lands of Belarus. Theoretical and methodological approaches to conducting historical research on border regions are being developed. The relevance of the article is due to the activation of modern integration processes.